The diversity of entrepreneurial regimes in Europe - Selin Dilli; Niklas Elert (Research Institute of Industrial Economics (IFN), 2016)
Although institutional reforms are necessary to increase rates of entrepreneurship in European countries, we argue that one-size-fits-all reform strategies are unlikely to be successful. Reform strategies must be informed by a better knowledge of the varieties of European capitalism and the institutional complementarities that drive these differences. We investigate these issues by gathering a number of potentially relevant entrepreneurial regime measurements as well as indicators of formal and informal institutions based on data available from the 2000s onward. We employ principal component analysis, factor analysis and cluster analysis to examine how 21 European countries and the United States cluster in the entrepreneurial and institutional dimensions. Our results reveal six country clusters, or entrepreneurial regimes, with a distinct bundle of entrepreneurial characteristics and institutional attributes. The main implication is that different reform strategies are appropriate to promote entrepreneurship and economic growth in European countries in different clusters.
Keywords: L5; M13; O31; P14; 330; Entrepreneurship; Innovation; Institutions; Regulation